Big Brother as a Contract Monitor: An Assessment of the Use of Contract Staff to Monitor Offender Communications - Dierenfeldt, Rick (American journal of criminal justice, 2016)
The privatization of prison services is a growing trend in the field of corrections; however, this growth has not been matched by evaluative research. This study examines the use of contract staff to supplement state intelligence investigators’ efforts to monitor outgoing offender telephone communications for evidence of illicit activity at 18 adult institutions in a Midwestern department of corrections. Percent-change models and Autoregressive Integrated Moving Average (ARIMA) modeling are used to examine aggregates of intelligence reports documenting drug, expressive, instrumental, and administrative violations. Our findings indicate that the introduction of contract services was associated with substantial increases in the number of intelligence reports filed within each of these categories. Furthermore, these results suggest that the use of privatized services that supplement rather than replace public efforts appear to be an ethical, efficient, and cost-effective alternative to comprehensive privatization.